2014
DOI: 10.1002/aoc.3117
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐functionalized niobocene complexes

Abstract: 4 ) was synthesized and characterized by electron paramagnetic resonance. Three structures were determined by X-ray diffraction analysis and revealed the expected bent metallocene structure with two cyclopentadienyl ligands and two chlorides coordinated to niobium in the oxidation state IV. Chlorides and the centroids of the η 5 -bonded cyclopentadienyl rings define a distorted tetrahedron. The cytotoxicity study has demonstrated that substitution with methoxybenzyl groups can lead to highly active species, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…235 More recently, the powerful superhydride reagent LiBEt 3 H has been widely applied to a large variety of 6-arylfulvenes. This method readily gives access to the corresponding lithium cyclopentadienyl precursors for direct use in the synthesis of titanocene, 236−246 zirconocene, 247 vanadocene, 248−250 niobocene, 251 molybdocene, 252 and tin 253 complexes (Scheme 87).…”
Section: Pentafulvenes As Precursors For Cp Ligandsmentioning
confidence: 99%
“…235 More recently, the powerful superhydride reagent LiBEt 3 H has been widely applied to a large variety of 6-arylfulvenes. This method readily gives access to the corresponding lithium cyclopentadienyl precursors for direct use in the synthesis of titanocene, 236−246 zirconocene, 247 vanadocene, 248−250 niobocene, 251 molybdocene, 252 and tin 253 complexes (Scheme 87).…”
Section: Pentafulvenes As Precursors For Cp Ligandsmentioning
confidence: 99%
“…Strong effect of coordinated chelating ligand on in vitro cytotoxic activity of [(η 5 ‐Cp’)Mo(CO) 2 (L)][BF 4 ] has been well documented already in the early stage of investigation on mouse Ehrlich ascites tumor cells [18] and human MOLT‐4 leukemia cells [19] while effects of cyclopentadienyl (Cp) ligand substitution seemed to be negligible for a long time [19,20] as several substitution patterns brought only minor lowering of half‐maximal inhibitory concentrations (IC 50 ). Studies on MOLT‐4 cell line documented a high cytotoxicity for various species bearing modified Cp/Ind ring and following N,N’ ‐chelating ligands: 1,10‐phenanthroline (phen), 4,7‐diphenyl‐1,10‐phenanthroline (4,7‐Ph 2 Phen), 5‐amino‐1,10‐phenanthroline (5‐NH 2 Phen) [19–22] . Indenyl molybdenum compounds bearing 4,7‐Ph 2 Phen and 2,2’‐biquinoline (bq) exhibit high in vitro activity against human colorectal cancer cells HT‐29 and gastric cancer cells MKN45, GP‐202 and GP‐220 [18] .…”
Section: Introductionmentioning
confidence: 99%
“…(5-NH 2 Phen). [19][20][21][22] Indenyl molybdenum compounds bearing 4,7-Ph 2 Phen and 2,2'-biquinoline (bq) exhibit high in vitro activity against human colorectal cancer cells HT-29 and gastric cancer cells MKN45, GP-202 and GP-220. [18] However, scrutinizing a wider range of compounds bearing modified Cp/Ind ring has shown unusually high cytotoxicity against MOLT-4 and HL-60 leukemia cells for particular complexes of 2,2'-bipyridine (bpy) [23] even though parent cyclopentadienyl species [(η 5 -Cp)Mo(CO) 2 (bpy)][BF 4 ] is almost inactive.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique conjugated systems, fulvene derivatives are very important for the synthesis of natural products and metallocene complexes. In our previous works, we found that 6′-hydroxyfluvene 1 was almost the exclusive form in the equilibrium with 1-1, because it could be stabilized by intramolecular hydrogen-bonding (Scheme ). Compound 1 can readily react with n -butylamine to give amination product 3 - 1 . , On the basis of the result, we continued to study regioselectivity in the chlorination reaction of 6′-hydroxyfluvene 1 by treating it with POCl 3 and DMF.…”
Section: Introductionmentioning
confidence: 99%